Therapeutic Proteins Methods and Protocols - Smales, C. Mark.; Smales, C. Mark.; James, David C.; James, David C. (Methods in Molecular Biology,, 2005)
With the completion of the human genome, the number of protein-based drug candidates has increased dramatically, along with the need to find methods for producing these proteins on a scale large enough to meet demand without compromising the authenticity of the final product. In Therapeutic Proteins: Methods and Protocols, world-class researchers share their innovative and proven techniques for the production of therapeutic proteins downstream of the discovery stage. The methods use a variety of sources for producing therapeutic proteins, including bacterial and yeast expression systems, and insect and mammalian cells, and then cover the purification of the resulting protein using both state-of-the-art and traditional methods, such as those sourced from plasma. Additional chapters offer methods for the characterization of therapeutic proteins throughout the production process, along with methods and strategies for viral inactivation and protein formulation. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Authoritative and highly practical, Therapeutic Proteins: Methods and Protocols offers both novice and experienced researchers the latest innovative, readily reproducible techniques, as well as helpful commentaries on the development and production of therapeutic proteins, ranging from their expression to actual formulation.